2018
DOI: 10.3389/fphys.2018.00919
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Modified Shuttle Test to Predict Peak Oxygen Uptake in Youth Asthma Patients Under Regular Treatment

Abstract: Background: Oxygen uptake (VO2) evaluations by cardiopulmonary exercise test is expensive and time-consuming. Estimating VO2 based on a field test would be an alternative.Objective: To develop and validate an equation to predict VO2peak based on the modified shuttle test (MST).Methods: Cross sectional study, with 97 children and adolescents with asthma. Participants were divided in two groups: the equation group (EG), to construct the equation model of VO2peak, and the cross-validation group (VG). Each subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…However, this method requires costly equipment, specialized training, and is not always available in clinical practice (Society, 2003), especially in developing countries. Thus, it is often necessary to determine exercise capacity using field tests and the MST is considered a simple, externally paced, and incremental (progressive increase of velocity) test (Lanza et al, 2018). Several studies (Costa et al, 2018; Labadessa et al, 2018; Lanza et al, 2018; Vendrusculo et al, 2019) have demonstrated good correlations between the distance achieved in the MST and the VO 2 obtained during CPET, both in respiratory diseases and in other clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this method requires costly equipment, specialized training, and is not always available in clinical practice (Society, 2003), especially in developing countries. Thus, it is often necessary to determine exercise capacity using field tests and the MST is considered a simple, externally paced, and incremental (progressive increase of velocity) test (Lanza et al, 2018). Several studies (Costa et al, 2018; Labadessa et al, 2018; Lanza et al, 2018; Vendrusculo et al, 2019) have demonstrated good correlations between the distance achieved in the MST and the VO 2 obtained during CPET, both in respiratory diseases and in other clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is often necessary to determine exercise capacity using field tests and the MST is considered a simple, externally paced, and incremental (progressive increase of velocity) test (Lanza et al, 2018). Several studies (Costa et al, 2018; Labadessa et al, 2018; Lanza et al, 2018; Vendrusculo et al, 2019) have demonstrated good correlations between the distance achieved in the MST and the VO 2 obtained during CPET, both in respiratory diseases and in other clinical conditions. Recently, one study (Lanza et al, 2018) showed a strong correlation between the MST and VO 2 (87% prediction power) in children and adolescents with mild/moderate asthma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations